The Influence of Perceived Price on Revisit Intention through Social Influence for Adaptive Reuse Building in the Old City of Jakarta - Anita Maulina; Rita Budiarti; Budiana Ruslan; Nur Fitri Rahmawati (Ilomata International Journal of Social Science, 2022)
Kota Tua, also known as old Batavia (Old Batavia) was inaugurated as a cultural heritage site by the governor of Jakarta, Ali Sadikin, in 1972. In order to improve Jakarta's Old City area, the government is currently strengthening the revitalization and adaptive reuse process as a goal in increasing long-term investment, as a tourism area for the tourism sector, and as a promotion of cultural diversity while maintaining the character and value of the historical value of the Old City area. The type of research used in this study is a type of descriptive research with quantitative approach method. Which method of data collection in the form of observation, distribution of questionnaires, and literature study. The population in this study is visitors to the Old City area of Jakarta and the sample size of 261 respondents. The sampling technique used is purposive sampling, that is, those who have ever visited the Old City area of Jakarta. The results showed that perceived price has a positive influence on social influence, social influence has a positive influence on revisit intention, perceived price has a positive influence on revisit intention, and social influence is also a mediation between perceived price and revisit intention.